LAS NUEVAS TECNOLOGÍAS DE INFORMACIÓN Y COMUNICACIÓN EN LA EFICACIA DE LA FORMACIÓN PROFESIONAL UNIVERSITARIA DEL LICENCIADO EN ADMINISTRACIÓN DE LA UNMSM - Tezén Campos, José Hugo (2014)
To demonstrate the contribution of new information and communication technologies on the effectiveness of university training of Administration Degree in San Marcos , own techniques of scientific research and document analysis , surveys and applied instruments to determine perceptions of direct users of educational services in the unit of analysis in order to answer the research question posed as follows: To what extent the new information and communication technologies contribute to achieving effectiveness of university training of Administration Degree in San Marcos? Problem that motivated the overall objective that states: Determine the level of contribution of new information and communication technologies to achieve efficiency of university training Lic Management San Marcos. To achieve the objective we considered the following methodology: a. First, the unit of analysis for conducting research is the career management of National University of San Marcos is determined. b. Document analysis of curriculum career and determination of technological platforms. c. Application of data gathering instruments, to direct users to determine levels of use of new information and communication technologies in vocational training Degree in San Marcos administration, data were processed with SPSS software. Then he proceeded to analyze the results obtained for the purpose of responding to the problem, through the assumption that the new information and communication technologies contribute to achieving effectiveness of university training of Management Accountant of San Marcos, which finally investigated compared with the objectives that led to its achievement.